Study of the effects of spray-drying on the functionality of probiotic lactobacilli - Paez, Roxana (2013)
Three probiotic lactobacilli strains were spray-dried in 20% (w/v) skim milk and submitted to a simulated gastrointestinal digestion. Fresh or spray-dried cultures were administered to mice for 5 and 10 days, and Immunoglobulin A (IgA)-producing cells were enumerated in the small intestine by immunohistochemistry. Spray-drying significantly enhanced the resistance of Lactobacillus paracasei A13 and Lactobacillus casei Nad to a simulated gastrointestinal digestion (0.96 and 1.95 log orders, respectively), compared with fresh cultures. Also, a significant higher number of IgA-producing cells were induced by spray-dried cultures compared with fresh cultures. Spray-drying is a suitable, but strain-dependent, technological process for the development of probiotic cultures in skim milk with increased functionality.